10 participants completed Fibre Optic Course training successfully obtained jobs - Siti Nur Azwin, Zulkapri (UMPSA, 2023)
PAYA BESAR, 15 December 2022 - A total of ten participants of the Fibre Optic Course Training Programme sponsored by the Pahang Islamic Religious and Malay Customs Council (MUIP) in collaboration with UMP Advanced Education (UMP Advanced) successfully completed their training and started work in the field of fibre optic in Temerloh and Bentong, Pahang.